Analysis of Convective Cloud Distribution Patterns Using The Himawari-9 Satellite Red Green Blue (Rgb) Method in The Cenderawasih Bay Coastal Region in 2023 - Sampe, Eusebio Andronikos; Hayati, Noorlaila (International Journal Labs, 2025)
Cenderawasih Bay, located near the equator, is characterized by a local rainfall pattern largely influenced by the development of convective clouds along its coastal areas. This study aims to analyze the distribution patterns of convective clouds in the coastal region of Cenderawasih Bay using data from the Himawari-9 meteorological satellite. The research method employed the RGB (Red Green Blue) composite technique using SATAID software to visualize and interpret convective cloud dynamics. The results show that during the June 2023 period, cloud-top temperatures ranged from -50°C to -70°C, with cloud movements predominantly from east to west. Convective clouds were primarily observed over the coastal areas of Manokwari, Biak, Serui, and Nabire, with cloud growth occurring mostly at night until early morning. The vertical development of clouds in this period reached heights between 3.1 km and 15.5 km. In contrast, during November 2023, convective cloud activity was significantly lower, mainly limited to Manokwari and Biak, with similar nocturnal growth patterns and cloud heights ranging from 1.8 km to 15.1 km. The RGB day convective storms composite effectively identified ice particles in cloud tops, linking cloud distribution with potential rainfall events. The RGB 24-hour microphysics product was also useful in monitoring cloud-top temperature variations to assess severe weather potential. These findings demonstrate the effectiveness of satellite-based RGB analysis in monitoring convective activity and its relation to localized precipitation, providing valuable insight for weather forecasting and disaster preparedness in the region.